Daoism and Wu. Issue 10 (October 2014) - Chai, David
Abstract This paper introduces the concept of nothingness as used in classical Daoist philosophy, building upon contemporary scholarship by offering a uniquely phenomenological reading of the term. It will be argued that the Chinese word wu<inline-graphic xlink:href="ark:/27927/pgh1fd4rmsz" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> bears upon two planes of reality concurrently: as ontological nothingness and as ontic nonbeing. Presenting wu in this dyadic manner is essential if we wish to avoid equating it with Dao itself, as many have been wont to do; rather, wu is the mystery that perpetually veils Dao while serving as the root and counter‐balance to being, and yet, Dao also imbues things with wu to the extant that their physical makeup and usefulness, or lack thereof, can be traced back to their source in Dao. This does not only mean that Daoist cosmogony and metaphysics are inherently informed by nothingness/nonbeing instead of being/beings but that it works to unground all moral and epistemological norms in play, a feat no other school of thought in ancient China could accomplish.